HIV-Sheltering Platelets From Immunological Non-Responders Induce a Dysfunctional Glycolytic CD4+ T-Cell Profile - Zhu, Aiwei; Real, Fernando; Zhu, Jaja; Greffe, Ségolène; de Truchis, Pierre; Rouveix, Elisabeth; Bomsel, Morgane; Capron, Claude (Frontiers in Immunology, 2022)
Immunological non-responders (InR) are HIV-infected individuals for which the administration of combination antiretroviral therapy (cART), although successful in suppressing viral replication, cannot properly reconstitute patient circulating CD4+ T cell number to immunocompetent levels. The causes for this immunological failure remain elusive and no therapeutical strategy is available to restore a proper CD4+T cell immune response in these individuals. We have recently demonstrated that platelets harboring infectious HIV are a hallmark of InR and we now report on a causal connection between HIV-containing platelets and T cell dysfunctions. We show here that in vivo, platelets-T cell conjugates are more frequent among CD4+ T cells in InR displaying HIV-containing platelets (<350 CD4+ T cells/μl blood for > 1 year) as compared with healthy donors or immunological responders (IR, >350 CD4+ T cells/μl). This contact between platelet containing HIV and T cell in the conjugates is not infectious for CD4+ T cells as co-culture of platelets from InR containing HIV with healthy donor CD4+ T cells fails to propagate infection to CD4+ T cells. In contrast, when macrophages are the target of platelets containing HIV from InR, macrophages become infected. Differential transcriptomic analyses comparing InR and IR CD4+ T cells reveal an upregulation of genes involved in both aerobic and anaerobic glycolysis in CD4+ T cell from InR versus IR individuals. Accordingly, InR platelets containing HIV induce a dysfunctional increase in glycolysis-mediated energy production in CD4+ T cells, as compared with T cells cocultured with IR platelets devoid of virus. In contrast, macrophages metabolism is not affected by platelet contact. Altogether, this brief report demonstrates a direct causal link between presence of HIV in platelets and T cell dysfunctions typical of InR, contributing to devise a platelet-targeted therapy for improving immune reconstitution in these individuals.